Diverse crops, diverse Incomes: A concise guide to implement farmer-led crop budgeting in Bangladesh - Harun-Or-Rashid, Md.; Cheesman, Stephanie; Parupalli, Bharathi; Hossen Shanto, Maruf; Hossain, Md. Shakhawat; Krupnik, Timothy J. (TAFSSA, 2023)
Farmer-led crop budgeting can be a valuable tool for examining how individuals or groups of farmers utilize and generate resources during agricultural operations. Budgeting exercises enable the quantification and analysis of resource inputs and outputs for a particular operation, resource, or the entire farming enterprise. They can be particularly useful when comparing between alterative suites of diverse crops and cropping systems.